Pengaruh Model Problem Solving Terhadap Kemampuan Menyelesaikan Soal Matematika Berorientasi Hots pada Siswa Kelas IV SDS Yapsi Medan - Nurul Izzah; Ahmad Landong (Jurnal Dirosah Islamiyah, 2023)
This study aims to determine the effect of problem solving models on the ability to solve HOTS-oriented math problems in class IV SDS YAPSI Medan. The population in this study were all fourth grade students at SDS YAPSI Medan, which consisted of 3 classes, and 44 students were the sample in this study. This research is a Quasi-Experimental quantitative research with Nonequivalent Control Group research design. The instrument used in this study is a test. The results of this study were calculated using the SPSS version 25 application. From the results of the study, the average pretest score in the experimental class was 38.18 and the pretest in the control class was 36.36. After being given the pretest, the two classes were given different treatment, namely the experimental class using the problem solving model and the control class without using the problem solving model. Then did the posttest in both classes and the experimental class obtained an average value of 77.73 while the control class obtained a value of 49.32. Based on the results of hypothesis testing using the Independent T-test with the help of the SPSS version 25 application, t count 10.037 and t table 1.681, then t count > t table or 10.037 > 1.681 with a significant value of 0.001, a significant value (2 tailed) < α (0 , 05). And it can be concluded that H0 is rejected and Ha is accepted, meaning that there is a significant influence of the Problem Solving Model on the ability to solve HOTS-oriented math problems in class IV SDS YAPSI Medan. Keywords: Problem Solving Models; Problem Solving Ability; HOTS Oriented Mathematics.